Approaches to the formation of Public Administration in the Context of Decentralization Reform in Ukraine - Vasylieva, Nataliia V.; Vasylieva, Oleksandra I.; Prylipko, Sergii M.; Kapitanets, Svitlana V.; Fatkhutdinova, Olena V. (Cuestiones Políticas, 2020)
Based on the analysis of the works of national and international scientists and professionals available in the bibliography, the article aimed to reveal a conceptual vision of the application of innovative approaches to the training of public servants in a decentralized environment. Emphasis is placed on solving the urgent problem of public administration that is expressed in the professional capacity of those who form and implement public policies to solve socially significant problems under indeterminate conditions during the implementation of the decentralization reform in Ukraine. Methodologically, the text document analysis technique was used. The authors propose a professional training program for public servants, including community leaders, which is a synthesis of methodological techniques, as well as modern personnel technologies, such as: change management, design thinking, gender approach, human resource management , HR management, time management, etc. By way of conclusion, the convenience of using innovative approaches that meet the needs of each consumer of public services and can ensure effective and competitive development of the territories is verified. Furthermore, the article reveals the conceptual provisions that should form the basis of a new model of public service.